Impact of Integrated Thinking and Reporting on Organisational Decision Making: Case Study of Public Sector Enterprises in Oman - Amena Sibghatullah (LifeSciFi, 2018)
The purpose of this study is to determine the impact of integrated thinking and reporting on organisational decision making; Case study of Public sector Enterprises in Oman. This study was quantitative in nature in which the data has been gathered from 369 respondents through survey questionnaire. Besides, the researcher used the SEM model as the technique for analysing the data while determining the moderating effect along with path assessment and CFA. The findings of this research suggest that there is impact of Balancing Financial and Non-Financial Information was determined on the organisational decision making. Moreover, the external environment was determined to have significant moderator in the relationship of Balancing Financial and Non-Financial Information and Risk Identification and Management with organisational decision making. The study is limited to the public sector enterprise of Oman.